2008
DOI: 10.1002/macp.200700582
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Route for Polystyrene Grafted Single‐Walled Carbon Nanotubes and their Characterization

Abstract: A novel route to graft polystyrene from the surface of single walled carbon nanotubes has been discussed. Grafting of one styrene unit onto SWCNT sidewalls was successfully done by Friedel Craft acylation reaction using cheap and reusable ZnO catalyst. FT‐IR and Raman spectra and TGA show the effective grafting of styrene onto the SWCNT. End‐grafted polystyrene polymer was synthesized on the SWCNT surface by free radical polymerization. It is found that optimum monomer concentration, reaction temperature and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 50 publications
0
7
0
2
Order By: Relevance
“…FTIR spectrum of FSWNT-PS shows significantly reduced C−F peak and exhibits characteristic peaks of styrene at 760 and 3030 cm −1 , which correspond to the styrene ring vibration and C−H stretching of the aromatic ring, respectively (Figure S6). 28 1 H nuclear magnetic resonance (NMR) spectrum provided further evidence: peaks at δ = 6.4−7.2 ppm and δ = 0.8−2.1 ppm correspond to the phenyl proton and C−H groups of the polystyrene backbone, respectively (Figure S7). The thermogravimetric analysis (TG) showed that the overall weight loss of FSWNT-PS sample is ∼20% more than that of defluorinated FSWNTs, which was ascribed to the decomposition of PS chain on the sidewall of nanotubes (Figure S8).…”
Section: Nano Lettersmentioning
confidence: 99%
“…FTIR spectrum of FSWNT-PS shows significantly reduced C−F peak and exhibits characteristic peaks of styrene at 760 and 3030 cm −1 , which correspond to the styrene ring vibration and C−H stretching of the aromatic ring, respectively (Figure S6). 28 1 H nuclear magnetic resonance (NMR) spectrum provided further evidence: peaks at δ = 6.4−7.2 ppm and δ = 0.8−2.1 ppm correspond to the phenyl proton and C−H groups of the polystyrene backbone, respectively (Figure S7). The thermogravimetric analysis (TG) showed that the overall weight loss of FSWNT-PS sample is ∼20% more than that of defluorinated FSWNTs, which was ascribed to the decomposition of PS chain on the sidewall of nanotubes (Figure S8).…”
Section: Nano Lettersmentioning
confidence: 99%
“…2 In particular, a variety of living free radical polymerisation methodologies have been applied since carboxyl-modified carbon nanotubes can be easily functionalised with groups (e.g. polymerisable groups; 3 initiating alkyl halides; 4 chain transfer agents 5,6 ), which enable polymer chains to be grafted from their surfaces. Free radical polymerisation in the presence of RAFT agents has been used to produce polymers with narrow polydispersities.…”
Section: Introductionmentioning
confidence: 99%
“…21 Some researchers studied the surface coating of CNTs to improve the dielectric constant of the prepared composite samples. [22][23][24][25][26][27][28] Zhang et al prepared unique cyanate ester composites with high dielectric constant based on multifunctional CNTs coated with phosphaphenanthrene terminated hyperbranched polysiloxane. Qiang et al 29 prepared new high dielectric constant composites based on unique multibranched polyaniline and CNT hybrids, in which the multibranched structure, large polyaniline concentration and flexible Si-O chains make the multibranched polyaniline coated on surfaces of CNTs through -interaction and the CNT hybrids have good dispersion in epoxy matrix.…”
Section: Introductionmentioning
confidence: 99%